Analisis Kesalahan Berbahasa Indonesia: Studi Kasus pada Tiga Karya Makalah Mahasiswa Baru Prodi Pendidikan Akuntansi 2025: Penelitian - Janli Aman Saragih; Tri Bunga Arthaty; Dista Elvin Yanti Waruwu; Fitriani Lubis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine errors in the use of Indonesian language in the written work of new students in the Accounting Education Study Program in 2025. A qualitative approach was applied, utilizing content analysis of three student papers as samples. The findings revealed 76 cases of language errors that can be grouped into five categories, namely spelling (22 cases), punctuation (15 cases), diction (12 cases), ineffective sentences (18 cases), and paragraphs (9 cases). Spelling errors and ineffective sentences were the most prominent. The main causes of these errors included a lack of accuracy, the influence of spoken language habits that seeped into writing, and students' limited understanding of the rules of the General Guidelines for Indonesian Spelling (PUEBI) and academic writing skills. These results indicate that the writing skills of new students still need to be strengthened through proofreading practice, structured writing exercises, and language teaching that focuses more on practical application.